The Linguistic Practices in Social Media in the Algerian Context: between Human Relations Reinforcement and Hate Speech Proliferation - Benabed, Ammar (Technium Social Sciences Journal, 2022)
The current study is an attempt to address some of the issues surrounding social media use with more emphasis on their role in reinforcing human relationships and spreading hatred speech. For the sake of presenting a comprehensive overview of the issue, a blend of quantitative and qualitative methodologies was implemented in the present study to analyse presence and incidence of hate speech and friendly relationship discourse in social media. To embark on such endeavour, a mixed- method, encompassing both a questionnaire and corpus analysis, is adopted. The targeted sample of the questionnaire’s addressees consists of social media users (n=100) from different categories of people. The second tool comprises a set of messages, comments and posts that are collected from different social media, especially Facebook. The findings revealed that hate speech, based on ethnicity, race, tribe, skin color, religion and physical appearance, is becoming prevalent among social media users, surpassing the spread of human relationships.